2021
DOI: 10.4143/crt.2020.950
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility of ACE2 and TMPRSS2 in Six Common Cancers and Possible Impacts on COVID-19

Abstract: Purpose Coronavirus disease 2019 (COVID-19) pandemic has spread worldwide rapidly and patients with cancer have been considered as a vulnerable group for this infection. This study aimed to examine the expressions of angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) in tumor tissues of six common cancer types.Materials and Methods The expression levels of ACE2 and TMPRSS2 in tumors and control samples were obtained from online databases. Survival prognosis and biological func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Interestingly, cancer survivors had more likely to suffer disease complications than healthy people but less likely than cancer patients[ 98 ]. Recent studies describe a possible link between SARS-CoV-2 receptor ACE2 in cancer tissues and increased risk of infection[ 99 ]. In liver cancer, Dai et al [ 100 ] found that upregulated expression of ACE2, the primary SARS-CoV-2 ligand in infected cells, was related to improved survival in HCC patients.…”
Section: Liver Cancermentioning
confidence: 99%
“…Interestingly, cancer survivors had more likely to suffer disease complications than healthy people but less likely than cancer patients[ 98 ]. Recent studies describe a possible link between SARS-CoV-2 receptor ACE2 in cancer tissues and increased risk of infection[ 99 ]. In liver cancer, Dai et al [ 100 ] found that upregulated expression of ACE2, the primary SARS-CoV-2 ligand in infected cells, was related to improved survival in HCC patients.…”
Section: Liver Cancermentioning
confidence: 99%
“…Another similar study was conducted by Hoang et al [47] where they tried to assess the expression level of ACE2 and TMPRSS2 in 6 cancer types [Lung Adenocarcinoma (LUAD), Breast Invasive Carcinoma (BRCA), COAD, PRAD, STAD, and Liver Hepatocellular Carcinoma (LIHC)] and compared those values found in malignancies to that of non-cancer patients. With GEPIA2 [33] , they found that mRNA levels of ACE2 expression were significantly higher in COAD and STAD which is similar to the findings of Li et al [32] .…”
Section: Genetic Interlinks Between Cancer and Covid-19mentioning
confidence: 99%
“…Another interesting fact is that they tried to narrow down the affected pathways. KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment analysis for ACE2 and top 100 co-expressed genes showed that the most significant pathways were phenylalanine metabolism (p=0.003), tryptophan metabolism (p=0.001), vitamin digestion and absorption (p < 0.001), steroid hormone biosynthesis (p=0.003), fat digestion and absorption (p=0.001), and Renin-Angiotensin System (RAAS) (p=0.006) [47] . Such extensive involvement of metabolic pathways was also supported by a metabolism-linked hypothesis regarding NAMPT/ NAD and RAAS and this hypothesis seems to materialize a connection between cardiovascular function [48] , lung failure and [49] SARS infections [50] .…”
Section: Genetic Interlinks Between Cancer and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatics studies of COVID-19 and cancer focus on the expression in cancers of key factors such as angiotensin-converting enzyme 2 (ACE2), transmembrane serine protease 2 (TMPRSS2), and neuropilin-1 (Chai et al 2020 ; Ahmadi et al 2021 ; Hoang et al 2021 ; Hu et al 2021a ), although few studies report a common genetic signature of COVID-19 and cancer, particularly of patients with LUAD, as well as potential underlying biological processes. Understanding the common genetic features between these two diseases and the underlying biological processes can help to explore the pathophysiological processes in patients with both diseases, improve the medical management of these patients, and allow the search for appropriate treatment modalities and medclines.…”
Section: Introductionmentioning
confidence: 99%